THEORETICAL ANALYSIS OF THE PSYCHOLOGICAL PHENOMENON "TOLERANCE TO VAGUENESS" - Tomarzhevskaya, I. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article deals with the theoretical analysis of the phenomenon of tolerance to uncertainty in foreign and domestic psychological studies, specifying its content. An attempt was made to reveal the structure of this phenomenon, analyze the approaches to its study, the history of the formation of a construct. The psychological peculiarities of the situation of uncertainty and the role of uncertainty situations in the development of personality are considered.Tolerance for vagueness is a scientific construct with many interpretations. The author focuses on a number of approaches which have developed during the study of this phenomenon: tolerance for vagueness as a personality trait, tolerance for vagueness as a situation-specific disposition, tolerance for vagueness as a metacognitive process and a skill. It is noted that the integration of a construct "tolerance-intolerance for vagueness".
Keywords: tolerance towards vagueness, intolerance towards vagueness, personal construct, personality trait